Efektivitas Konseling Kelompok Teknik Self-Instruction Untuk Mereduksi Kejenuhan Belajar Siswa SMP Negeri 9 Banjarbaru - Rabin Rahim; Rudi Haryadi (Medan State University, 2022)
This study aims to determine the effectiveness of group services using self-instruction techniques in overcoming the boredom of learning in seventh grade students of SMP Negeri 9 Banjarbaru. This study uses an experimental quantitative research method that examines the effectiveness of group counseling services with self-instruction techniques on the learning saturation of class VII students of SMP Negeri 9 Banjarbaru, the measurements were carried out twice, namely before and after being given treatment with a measurement tool using a questionnaire/questionnaire and the subject in this study were seventh grade students of SMP Negeri 9 Banjarbaru. After the research was conducted and the results obtained from the implementation of the self-instruction technique group counseling service intervention to students who had a high level of learning saturation. For this reason, the intervention was given to students with a high level of learning saturation and with group counseling service interventions using self-instruction techniques.